2018
DOI: 10.1080/13546783.2018.1523808
|View full text |Cite
|
Sign up to set email alerts
|

The logic sense: exploring the role of executive functioning in belief and logic-based judgments

Abstract: The Default Interventionist account suggests that by default, we often generate belief-based responses when reasoning and find it difficult to draw the logical inference. Recent research, however, shows that in some instances belief judgments take longer, are more prone to error and are more affected by cognitive load. One interpretation is that some logical inferences are available automatically and require intervention in order to respond according to beliefs. In two experiments, we investigate the effortful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 41 publications
6
16
0
Order By: Relevance
“…This account claims that, depending on the complexity of the task at hand, T1 processes have access to the underlying logical structure of the problem and interestingly, on simple reasoning problems, the logical structure of a statement is more accessible than other features like its believability . The fast logic hypothesis of this model is consistent with the observation of higher accuracy and lower speed for logic judgments (Handley et al, 2011;Pennycook, Trippas, et al, 2014) and the relative immunity of logic judgments from cognitive loading compared to belief judgments Howarth et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…This account claims that, depending on the complexity of the task at hand, T1 processes have access to the underlying logical structure of the problem and interestingly, on simple reasoning problems, the logical structure of a statement is more accessible than other features like its believability . The fast logic hypothesis of this model is consistent with the observation of higher accuracy and lower speed for logic judgments (Handley et al, 2011;Pennycook, Trippas, et al, 2014) and the relative immunity of logic judgments from cognitive loading compared to belief judgments Howarth et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…The main goal of Experiment 1 was to investigate whether conflict interferes with belief judgments on both logical and pseudo-logical arguments. Consistent with numerous findings in the literature, we found that a conflict between the logical validity and believability of a conclusion affected both accuracy and confidence ratings under both belief and logic instructions (Handley et al, 2011;Howarth et al, 2018;Ricco et al, 2020;Thompson et al, 2018;Trippas et al, 2017): Participants were less accurate and less confident on conflict arguments than non-conflict arguments. Under belief instructions, this sensitivity to conflict has been considered to be evidence for logical intuition (Handley & Trippas, 2015;Trippas & Handley, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…However, belief interfered with logic judgments to the same extent for both cognitive ability groups. Consistent with Experiment 2, this finding supports the notion that individual differences in logical intuition cannot be explained by variation in cognitive ability (Ghasemi et al, 2021;Howarth et al, 2018;Markovits et al, 2020;Morsanyi & Handley, 2012).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations